Southeast Asia in political science theory, region, and qualitative analysis - Kuhonta, Erik Martinez; Slater, Dan; Vu, Tuong (East-West Center series on contemporary issues in Asia and the Pacific, 2008)
This book provides a state-of-the-art review of Southeast Asian political studies through a dialogue involving theoretical analysis, area studies, and qualitative methodology.